GNSS and accelerometers data fusion in large structures monitoring - Lima, J. N. (2017)
The monitoring systems have two main objectives: (i) to evaluate the safety conditions and durability of the infrastructures and to develop a better understanding about their day-to-day behaviour; (ii) to detect the occurrence of special events that might jeopardize the safety of the structure. To reach the first objective it is mandatory to create a database as most extensive as possible to support an analysis of the structural behaviour. Regarding the second objective near real-time automatic systems must be created in order to analyse the recorded data and establish limits of alert with alarm warnings when those limits are exceeded. This R&D project aims to develop a measurement system, based on GNSS (Global Navigation Satellite Systems), suitable to monitor large scale civil engineering structures and infrastructures, particularly bridges and dams. This monitoring system final objective is to measure the displacements of some selected points of the structures. These points should be the most important ones to characterize the general behaviour of the monitored structure. The advantages of using a GNSS system are undeniable: this equipment is robust, operates under all weather conditions, does not require intervisibility between the monitored points and the reference points, uses an external tridimensional reference systems, and provides an extremely accurate time-reference frame. The GNSS positioning is affected by a numerous set of errors due to natural and artificial phenomena. These errors should be reduced as much as possible, in order to obtain good estimated distances between the observed satellites and the antenna of the receivers. There are well known observation and observation combination techniques (phase differences measurements, relative positioning and Precise Point Positioning - PPP) that allow to strongly reduce, or sometimes even eliminate, most of the errors. Using carefully selected observation and processing techniques it is possible to obtain high-precision GNSS positioning. The RTK (Real Time Kinematics) is the more recent high-precision positioning GNSS technique. It allows us to obtain high quality coordinates in almost real-time. When used in conjunction with top grade receivers (able to do observations at high frequencies) the RTK seems to be able to monitor high frequencies displacements of structures. Unfortunately the positioning precision is only at the centimetre level. To reduce this uncertainty it will be used short baselines and processing techniques based on the use of various filters and methodologies for multi-sensor observations fusion. It is precisely in the development of these techniques that the actual research project is focused. After the monitoring system specification, several techniques will be developed and tested in order to be included in a reliable measurement system that will meet the specified requirements. To define the monitoring system demands the following items have been addressed: - Requirements of the monitoring system in view of the behaviour of the selected structures; - Acquisition of know-how on data acquisition systems and in-site monitoring equipment; - Identification, characterization and analysis of software available for data processing.